Polysaccharides From Pogostemon cablin (Blanco) Benth.: Characterization and Antioxidant Activities - Zhao, Lei; Wang, Lei; Guo, Zimeng; Zhang, Ning; Feng, Qisheng; Li, Bo (Frontiers in Pharmacology, 2022)
Two polysaccharide fractions from Pogostemon cablin (Blanco) Benth. (P. cablin) (designated as PCB-1 and PCB2-1) were isolated by water extraction and purified by Sepharose chromatography. The chemical properties of the polysaccharides were characterised, and their antioxidant activities were evaluated. The sugar content of the crude polysaccharide (PCB), PCB-1, and PCB2-1 was 58.74%, 90.23% and 88.61%, respectively. The molecular weights of PCB-1 and PCB2-1 were determined to be 97.8 and 12.8 kDa, respectively. Monosaccharide composition analysis showed that all the three polysaccharides consisted of mannose, rhamnose, galacturonic acid, galactose, glucose, and arabinose, but with varying molar ratios. The polysaccharides exhibited significantly high antioxidant activities in vitro based on the scavenging activity against hydroxyl radicals, metal ion-chelating and ferric-reducing abilities. In vivo experiments in an oxidatively damaged mice model showed that PCB-1 increased the levels of antioxidant enzymes, including superoxide dismutase, catalase, and glutathione peroxidase, and inhibited malondialdehyde formation in the serum and liver. These findings suggest that PCB-1 has significant potential as an antioxidant in functional foods.